2013
DOI: 10.1111/1467-6427.12011
|View full text |Cite
|
Sign up to set email alerts
|

Patients' characteristics and the quality of the therapeutic alliance in family‐based treatment and individual therapy for adolescents with anorexia nervosa

Abstract: This study examines the relationship between patients' characteristics and the therapeutic alliance in family-based therapy (FBT) and adolescent focused therapy (AFT) for adolescents with anorexia nervosa (AN). Independent observers rated audiotapes of therapy sessions using the working alliance inventory-observer version (WAI-o). Patients' characteristics examined to predict the development of the therapeutic alliance included their socioeconomic characteristics, markers of eating disorder psychopathology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(51 reference statements)
3
8
0
Order By: Relevance
“…Overall and subscale WAI‐O scores were comparable to those typically obtained in other clinical trials (LoTempio et al., ). The total score for early session alliance was mean ( M ) = 182.0 (standard deviation [ SD] = 10.7) and late session alliance was M = 175.8 ( SD = 28.4).…”
Section: Resultssupporting
confidence: 80%
“…Overall and subscale WAI‐O scores were comparable to those typically obtained in other clinical trials (LoTempio et al., ). The total score for early session alliance was mean ( M ) = 182.0 (standard deviation [ SD] = 10.7) and late session alliance was M = 175.8 ( SD = 28.4).…”
Section: Resultssupporting
confidence: 80%
“…Moreover, the parents and therapists may have placed greater value on challenging the AN during the family meal given these patients' heightened illness severity. LoTempio et al () found that EDE scores at baseline were positively associated with the therapeutic alliance at session four of Maudsley FBT. The authors suggested that higher EDE scores could represent a greater acknowledgement of symptoms and an increased willingness to obtain help, which may contribute to patient–therapist collaboration during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There was a special issue of the Journal of Family Therapy (volume 35, issue supplement 1) on adolescent eating disorders with a review of the evidence base (Downs and Blow, ) and articles on the therapeutic alliance (LoTempio et al . ), multiple family therapy (Hollesen et al . ; Mehl et al .…”
Section: Developments In Family Therapy Practicementioning
confidence: 99%
“…There was a special issue of the Journal of Family Therapy (volume 35, issue supplement 1) on adolescent eating disorders with a review of the evidence base (Downs and Blow, 2013) and articles on the therapeutic alliance (LoTempio et al 2013), multiple family therapy (Hollesen et al 2013;Mehl et al 2013), a family admission programme (Wallis et al 2013) and a day hospital programme (Girz et al 2013). These articles highlight the value of family therapy in the treatment of adolescent eating disorders.…”
Section: Family Therapy For Adolescent Eating Disordersmentioning
confidence: 99%